Effectiveness Test of Spray Gel Hand Sanitizer with Carbomer 940 as a Preventive Product in Emergency Conditions - Sutiswa, Shandra Isasi; Aji, Nur; Yulia, Nunung (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Hand sanitizer is known for its ability to kill germs quickly due to its alcohol content, making it more effective than washing hands with soap and water. However, excessive use of alcoholbased sanitizers can cause skin irritation and dryness. Alcohol is polar and volatile, leading to rapid skin dryness and reduced effectiveness. To address this, gelling agents like Carbomer 940 are added to spray gel formulations. Carbomer 940 offers high stability and low toxicity, thereby enhancing the gel’s antibacterial properties. This study aims to develop an innovative spray gel hand sanitizer using Carbomer 940. The research method used was a pure experiment, evaluating the % inhibition of microbial growth on agar media. Results showed that the spray gel with 0.05% Carbomer 940 had superior effectiveness, with 60.77% inhibition, compared to the control group using the WHO formula, which achieved 33.11%. Additionally, the spray gel had a pH of 6.5 ± 0.2, a viscosity of 135.10, and an average spray weight of 0.027 ± 0.000 g, demonstrating optimal physical quality. In conclusion, the spray gel hand sanitizer with 0.05% Carbomer 940 was more effective at inhibiting microbial growth than the WHO standard formula.